Promoting employment, food security and nutrition in Mozambique. Sweetpotato-based job-opportunities for young people. Project profile. - International Potato Center (International Potato Center, 2019)
This project takes a novel approach to enhancing food security and incomes by focusing on employment opportunities. Through learning about growing, multiplying and processing orange-fleshed sweetpotato, young people in northern Mozambique will acquire the knowledge and skills to build sustainable livelihoods and contribute to food security and nutrition in their communities.